PEMBERDAYAAN IBU-IBU PKK MELALUI INOVASI PRODUK UMKM DI KELURAHAN TANAH PAK LAMBIAK - Silvia Nurul Reskika; Syanata Naylani; Zulaiha Zulaiha; Sovia Susanti; Nadila Aviska; Dinda Lisyo Putri; Indrianti Saputri; Rebeca Delavanni; Athifatul Husna; Rhandi Rizaldi; Abdul Mukhtar; Yulia Ningsih (ASOSIASI IDEBAHASA KEPRI, 2026)
The Community Service Program (PKM) for PKK members focused on improving their abilities and ingenuity in transforming local produce, specifically kale, into products that are both attractive and commercially viable. The program featured instruction in food processing methods, the creation of product ideas, and basic packaging techniques designed to emphasize local identity. Despite being a one-time event, participants demonstrated strong eagerness to utilize their newfound knowledge and investigate further business possibilities. Throughout the program, increased motivation to innovate, greater self-assurance, and a recognition of the value of creativity in product design were observed. These results demonstrate that PKM serves not only as an educational opportunity, but also as a catalyst for encouraging initiative, creative thinking, and a continued drive to build participants’ businesses. Ultimately, PKM delivers hands-on experience that empowers PKK members and promotes the expansion of local micro, small, and medium-sized enterprises.